The effects of cGnRH on gonadotropin secretion and hatching traits in Japanese quail - ÇIFTCI, HB; AYGÜN, A (Journal of the Hellenic Veterinary Medical Society, 2022)
The aim of this study was to measure the effect of chicken Gonadotropin Releasing Hormone-I (cGnRH-I) on male fertility potential. Male and female quails were placed in cages(1 male and 5 females) and devoted into four experimental groups: a) control group - no injection, b) negative control group - 200 μl standard saline was injected, c) 5μg cGnRH group - 5μg cGnRH-I was injected and d) 20μg cGnRH group - 20μg cGnRH-I was injected. Each group was consisting of scattered six cages. In each cage only males were subcutaneously injected under the wing (3 injections - 1 week apart from each other). A fourth injection was administered at the end of egg collection and one hour later blood was collected and serum concentrations of Luteinizing Hormone (LH), Follicle Stimulating Hormone (FSH), prolactin and testosterone were measured. Egg fertility, hatchability and weekly egg production per hen were also measured. Injection of cGnRH-I did not increase pituitary gonadotropin secretion (LH or FSH); however, serum LH concentration non-significantly reduced in negative control group. A significant decrease in serum testosterone concentration was observed in negative control group compared to 20 μg cGnRH injected group. Fertility and hatchability of total set eggs were lower in negative control group compared to other groups. Egg production in control group was significantly decreased, probably due to the non-significant suppression of prolactin. Embryonic mortality (hatchability of fertile eggs) non-significantly increased in control and negative control groups compared to GnRH injected groups. It seems that cGnRH has a positive effect on fertility and hatchability; however, more studies are needed with older males to confirm our findings.